Negosiasi dalam Pelaksanaan Ritual Kaago-Ago Liwu pada Masyarakat Desa Lasiwa Kecamatan Wakorumba Utara - La Ode Sahidin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2014)
The ritual tradition kaa-ago Liwu is a ritual as a form of communication to the metaphysical beings to beseech for safety and avoid the disaster. The ritual is held at every turn east to west monsoon season or vice versa. The ritual is conducted in Lasiwa village and it consists of two types: first is namely katingka which is held on designated place and the second is in the form of four-night dhikr rituals performed in the mosque. Both of the rituals are held simultaneously without any disappointed party. This can happen due to be able to establish arelationship of indigenous elite negotiations with other parties. Keywords: negotiation, ritual, kaago-ago liwu, custom elite